PENGARUH PENGGUNAAN TEPUNG JAHE MERAH SEBAGAI FEED ADDITIVE TERHADAP BERAT KARKAS, LEMAK ABDOMINAL DAN VICERAL (HATI, USUS DAN GIZZARD) PADA AYAM PEDAGING - Igo, Maria Thomasin (Jurnal Sains Peternakan, 2014)
Result of research of indicated that addition of red ginger flour as additive feed into broiler feed didn,t give influence  to carcass weight, abdominal fat weight,  visceral weight ( liver, and intestine of gizzard). Research having taken steps, result of research of  amount  highest carcass weight there are at treatment of  1.48 kg and hereinafter partake - partaking is  1.35 kg ,  1.20 kg, 1.18 kg  and 1.03 kg At abdominal fat of highest weight is  25 g, and hereinafter partake - partaking is 122.5 g,  20 g , 17.5 g  and  15 gr , result of obtained analysis during research to heavy hearted is  82.5 g and low is 55.0 g, at highest intestine weight there are at 122.5 g and low there are at  97.5 g while weight of gizzard highest is  60 g  and hereinafter partake - partaking is  52.5 g,  50 g,  50 g and  42.5 g. Concluded of that this usage research of red ginger flour as additive feed into broiler feed give influence which do not differ reality to carcass weight, abdominal fat weight, viceral weight roan ( liver, and intestine of gizzard). But at abdominal fat of excelsior of level gift/ giving hence progressively lower abdominal fat of him.Keyword        :           red ginger, additive of feed, carcass heavy, abdominal fat weight, weight viceral ( liver, and intestine of gizzard).